The impact of IS/IT strategy and business strategy alignment on business performance in the Palestinians firms - Mohammad Helaly (My University, 2012)
ABSTRACT The incredible growth of the information systems (IS) and information technology (IT) during the last two decades has clear, direct and huge impacts on all life sides, especially in the business. It is becoming a strategic enabler of new ways of doing business. Furthermore it plays the key role of doing business. It is involved in all business functions. In addition, Technology such as the internet and E-business has caused many companies to review their business and IT strategies and adopt the alignment philosophy to enhance their position, achieve business objectives and fully utilize the investment in the technology. According to studies reviewed information technology strategy and business strategy alignment is a hot topic. Moreover, it is considered as one of the top managers concerns. Alignment is a dynamic, complex process that takes time to develop and even more effort to sustain. This research aims to test if the alignment between IS/IT strategy and business strategy have an impact on the business performance in the Palestinians firms. To achieve this purpose the researcher used both qualitative and quantitative research methodologies. Qualitative data were collected via interviews with many CIO’s and CEO’s and consultants to make sure that our statistical findings agree with the reality of the Palestinian firms. Moreover, to provide a more description and understanding about the alignment in the Palestinian firms. In addition, the quantitative part based on previous research by titled “Alignment between business and IS Strategies, a study of prospectors analyzers and defenders”. Furthermore, data were gathered from the research population which consist of 46 Palestinians firms that are listed in the Palestine exchange via a survey. The response rate of survey was (46%). Results indicate that there is a positive correlation between business strategy and IS/IT alignment and business performance in the Palestinians firms, the correlation coefficient value was (0.27). Based on the research findings, Palestinian firm should perform studies and researches to determine the best business strategy that fits their business environment and fit the Palestinian market. Furthermore, Firms should focus more on the IS/IT strategies. Moreover, make studies and researches even take consultations before investment in IS/IT, to make sure that the new investment is right and fit the firm business strategy. Eventually, firms should Review the firm business strategy and IS/IT alignment continuously, and consider this process as management duty, due to the alignment impacts on improving business performance.

الملخص النمو المذهل لأنظمة وتكنولوجيا المعلومات في العقدين المنصرمين ، له اثار واضحة وكبيره على جميع جوانب الحياة وخاصة في الاعمال التجارية، هذا التطور أصبح محفز استراتيجي لتمكيننا القيام بالاعمال بشكل جديد، علاوة على ذلك، اصبحت أنظمة وتكنوليوجا المعلومات تلعب دورا جوهريا في تنفيذ العمل، واصبحت جزءا أساسيا في جميع اجزاء العمل. أجبرت التكنولوجيا مثل الانترنت والتجارة الاكترونية العديد من الشركات مراجعة إستراتيجيات الشركة واستراتيجية تكنولوجيبا المعلومات وإعتماد فلسلفة التوافق بينهم، لتعزيز مكانتهم بين المنافسين و وتحقيق أهداف العمل والاستفادة الكاملة من الاستثمار في التكنولوجيا. أكدت الدراسات السابقة ان موضوع التوافق بين استراتيجية (أنظمة المعلومات / تكنولوجيا المعلومات) واستراتيجية العمل هو موضوع مهم جدا ويعتبر واحد من اهم اهتمامات الادارة العليا. عملية التوافق هي عملية مستمرة ومعقدة وتستغرق وقت للتطور وتحتاج الى بذل الجهد للحفاظ عليها. يهدف هذا البحث إلى دراسة وتحديد أثر توافق استراتيجية (أنظمة المعلومات / تكنولوجيا المعلومات) وإستراتيجية العمل على أداء العمل في الشركات الفلسطينية، لتحقيق هذا الهدف تم استخدام منهجية البحث النوعي والكمي. وقد تم جمع البيانات النوعية من خلال المقابلات التي أجريت مع المدراء التنفيذيين ومدراء تكنولوجيا المعلومات والخبراء، للتأكد من مطابقة النتائج لواقع الشركات الفلسطينية والى زيادة وصف وفهم عميلة التوافق في الشركات الفلسطينية. الجزء الكمي من البحث يعتمد على دراسة سابقة، تم جمع البيانات الكمية من عينة البحث والتي تتكون من جميع الشركات الفلسطينيينة المدرجة في بورصة فلسطين وعددها 46 شركة باستخدام باستخدام طريقة الاستبانة حيث تم تصميمها وتوزيعها على كل إفراد العينة البحثية. وكان معدل استجابة العينة (46٪). تشير النتائج إلى أن هناك علاقة إيجابية بين توافق إستراتيجية (أنظمة المعلومات / تكنولوجيا المعلومات) وإستراتيجية العمل على أداء العمل الشركات الفلسطينية ، وبلغت قيمة معامل الارتباط (0.27). قام الباحث بناء على نتائج البحث بتقديم توصيات للشركة الفلسطينية بإجراء الدراسات والأبحاث لتحديد أفضل إستراتيجية عمل تتلاءم مع بيئتها التجارية وتناسب السوق الفلسطيني. وعلاوة على ذلك، يوصي بزيادة الشركات الفلسطينية التركيز على إستراتيجية تكنولوجيا المعلومات. يوصي الباحث أيضا، إجراء الدراسات والبحوث وإجراء الاستشارة اذا لزم قبل أي استثمار في تكنولوجيا المعلومات، للتأكد من أن هذا الاستثمار الجديد هو الصحيح والمناسب لإاستراتيجية عمل الشركة. أخيرا، يوصي الشركات بضرورة مراجعة التوافق بين إستراتيجية عمل الشركة وإستراتيجية (أنظمة المعلومات / تكنولوجيا المعلومات) بشكل مستمر، وإعتبار هذه العملية واجب من واجبات الإدارة، بسبب الآثار الايجابة المترتبة عن هذة العملية على تحسين أداء العمل.
أثر توافق استراتيجية (أنظمة المعلومات / تكنولوجيا المعلومات) وإستراتيجية العمل على أداء العمل في الشركات الفلسطينية